Indonesia Sistem Pengukuran dan Analisis Debit Air pada Kebocoran Pipa PDAM Rumah Tangga Berbasis Internet of Things - Dian Oktarisa; Meqorry Yusfi; Harmadi Harmadi (Jurnal Fisika Unand, 2025)
Pipe leaks in household PDAM systems often lead to water wastage and increased bills. This research develops a measurement and analysis system for water flow in household PDAM pipe leaks based on the Internet of Things (IoT) to address this issue. The system uses water flow sensors YF-S201 connected to a NodeMCU ESP8266 to measure water flow rates. It monitors two pipe branch areas, with each branch equipped with a water flow sensor at both the inlet and outlet points. The NodeMCU ESP8266 compares the incoming and outgoing water flow rates for each branch. If the flow rates are identical between the two sensors, the pipe is deemed safe; however, any discrepancy between the flow rates indicates a potential leak. The system can identify the area and severity of the leak based on the flow rate difference and calculate the water usage cost. Data collection is performed in the morning, afternoon, and evening, with six trials at each measurement time. The trials are conducted at 5-minute intervals to measure water volume and flow rate. Testing results show an average error percentage of 2.2% compared to a measuring cup, with system accuracy reaching 97.8%. Measurement data is displayed on an LCD and sent to the Blynk app via smartphone for remote monitoring.